Tocopherols, Polyprenols and Steroids from Passiflora edulis and Bioactivities of its Extractives - Aziz, Md Abdul; Ahsan, Monira; Hasan, Choudhury Mahmood; Masud, Mohammad Mehedi (Dhaka University Journal of Pharmaceutical Sciences, 2017)
?-tocopherol (1), ?-tocopherol (2), polyprenol-12 (3), polyprenol-15 (4), stigmasterol and ?-sitosterol were isolated from the yellow flavicarpa variety of leaves of Passiflora edulis. The structures of the isolated compounds were elucidated using 1H-NR and 13C-NMR spectral analysis. The organic and aqueous soluble fractions of crude methanolic extract were evaluated for the antioxidant, cytotoxic, thrombolytic and antimicrobial activities. In DPPH free radical scavenging assay, the aqueous soluble fraction displayed maximum activity having IC50 value of 139.56?g/ml. On the other hand, dichloromethane soluble fraction revealed maximum cytotoxic (LC50 24.17?g/ml) and thrombolytic (14.49% clot lysis) activities, when compared to the respective blanks. Dhaka Univ. J. Pharm. Sci. 16(1): 55-60, 2017 (June)